Targeting prefrontal cortex GABAergic microcircuits for the treatment of alcohol use disorder - Fish, Kenneth N.; Joffe, Max E. (Frontiers in Synaptic Neuroscience, 2022)
Developing novel treatments for alcohol use disorders (AUDs) is of paramount importance for improving patient outcomes and alleviating suffering related to the disease. A better understanding of the molecular and neurocircuit mechanisms through which alcohol alters brain function will be instrumental in the rationale development of new efficacious treatments. Clinical studies have consistently associated prefrontal cortex (PFC) function with symptoms of AUDs. Population-level analyses have linked PFC structure and function with heavy drinking and/or AUD diagnosis. Thus, targeting specific PFC cell types and neural circuits holds promise for the development of new treatments. Here, we overview the tremendous diversity in form and function of inhibitory neuron subtypes within PFC and describe their therapeutic potential. We then summarize AUD population genetics studies, clinical neurophysiology findings, and translational neuroscience discoveries. This literature collectively suggests that changes in fast transmission through PFC inhibitory microcircuits are a central component of ethanol’s neurobiological effects and the core symptoms of AUDs. Finally, we submit that there is a significant and timely need to examine sex as a biological variable and human postmortem brain tissue to maximize efforts in translating findings to new clinical treatments.